A Study of Psychological Distress Among Women with Polycystic Ovarian Syndrome in Kashmir - Bashir, Aadil; Najar , Shabir Ahmad; Ahmed , Sarafaraz; Shakeel, Afshana; Jan, Mehboob; Altaf, Mubashir (National Journal of Community Medicine, 2024)
Background: Polycystic Ovarian Syndrome, was previously thought to be an endocrine condition. Research has now demonstrated that polycystic ovarian syndrome affects a patient's quality of life and is a metabolic, hormonal and psychosocial condition. Women's joys are disrupted by PCOS because the stigma attached to hyperandrogenism is strongly felt and may harm women's psychological development. Methods: The aim of the study was to comprehend the psychosocial problems experienced by women in Kashmir and to obtain a thorough understanding of the coping mechanisms employed by women with PCOS. The research design was both qualitative and quantitative in nature. Thematic analysis was used to derive themes from the data. Sampling was purposeful in nature. Results: The study underscores that women with PCOS encounter numerous difficulties encompassing social and psychological aspects. Psychological issues like mood swings, stress, anxiety and sleeping disorders are prevalent among women with PCOS. Furthermore, the research has revealed that menstrual disorders significantly contribute to depression in women. The study also highlights a connection between infertility and psychological problems. Conclusion: In conclusion, the research underscores the multifaceted challenges faced by individuals with PCOS. Therefore, understanding these issues is crucial for developing effective coping mechanisms and improving the quality of life for women dealing with PCOS.